Vaccine confidence and hesitancy among mothers of children under six years of age in Salvador, Brazil: The role of sociodemographic factors and health service experience - Claudia Nery Teixeira Palombo; Ednir Assis Souza; Érica Marvila Garcia; Ráren Paulo da Silva Araújo; Lucas Regis de Oliveira Santos; Marcelle Lemos Leal; Aline Anne Cavalcante de Oliveira; Ana Paula Sayuri Sato; Clariana Vitória Ramos de Oliveira (PLoS ONE, 2026)
Background Vaccine hesitancy remains a pressing global health concern, particularly in early childhood, where delays or refusal to vaccinate can significantly compromise public health. Despite the recognized benefits of immunization, concerns about vaccine safety, efficacy, and necessity persist among some parents. We aimed to analyze vaccine hesitancy among mothers of children under six years old in Salvador, Bahia, Brazil. Method A cross-sectional study was conducted in 2023 involving 503 mothers of children under six registered at Family Health Units in Salvador. Data were collected through structured interviews assessing socioeconomic and health characteristics, vaccination status, and attitudes toward vaccines using a standardized questionnaire. Descriptive statistics and chi-square tests were used, with a significant level of 5%. Results Most mothers acknowledged the importance of vaccination, and over 80% expressed trust in vaccines; however, 27% demonstrated some degree of vaccine hesitancy. Higher maternal education (more than 11 years) was associated with greater vaccine confidence (β = −0.156, p = 0.002). In contrast, negative or neutral relationships with primary health care professionals were linked to lower trust and higher perceived vaccine risks (β = 0.123, p = 0.038). Mothers who declined new vaccines also showed significantly lower confidence in vaccination (β = 1.057, p = 0.002). Conclusions Although vaccine confidence is generally high, a substantial proportion of mothers still exhibit hesitancy—often influenced by educational level, healthcare relationships, and trust in newer vaccines. These findings highlight the need for targeted strategies that strengthen provider–parent relationships and build trust in vaccine safety to reduce hesitancy and protect child health.